Smart Feeder Berbasis IoT Menggunakan Sumber Energi Surya untuk Budidaya Ikan Berkelanjutan - Eko Sulistyo; Syaharani Rani; Daniel Nicholas Papilaya; Helda Susianti (ELECTRON Jurnal Ilmiah Teknik Elektro, 2026)
The rapid development of Internet of Things (IoT) technology has encouraged the adoption of automated systems in aquaculture to improve feed management efficiency. However, conventional fish feeding practices still rely on manual labor and grid-based electricity, leading to inefficiencies and sustainability concerns. This study aims to design and implement an IoT-based Smart Feeder powered by solar energy as an automated and environmentally friendly solution for fish farming. The system employs an ESP32 microcontroller as the main processing unit, an HC-SR04 ultrasonic sensor for feed-level detection, a servo motor and blower as feed distribution actuators, and an off-grid photovoltaic system consisting of a 100 Wp solar panel, a solar charge controller, and a battery for energy storage. The IoT system is integrated with a Flutter-based mobile application that serves as a user interface for remote monitoring and control via Firebase Realtime Database. System testing was conducted in a controlled environment, focusing on feed distribution performance, sensor accuracy, and solar energy system performance. The results indicate that the ultrasonic sensor achieved an accuracy of ±2 cm across three feed-level conditions. The system was able to distribute feed ranging from 220 to 550 grams with a throwing distance of 115–330 cm, depending on operation duration and pellet size. The solar panel generated a voltage of 20.3–21.2 V and supported autonomous system operation. These findings demonstrate the potential of integrating IoT and renewable energy to enhance automated fish feeding systems, although further testing in real pond environments is required